OBLIGATIONS OF SOLIDARITY OF SUBJECTS OF FORMATION AND IMPLEMENTATION OF FAMILY POLICY - Antonova , O. (Theory and Practice of Public Administration, 2020)
The article reveals the essence of the joint responsibility of the subjects of the formation and implementation of family policy, which, according to the author of the article, means the joint responsibility of the participants in the interaction process – the family, the state and society for mutually acceptable decisions in family policy. Joint and separate fulfillment of obligations provides for: a) indivisibility of the subject of actions; b) a clear division of responsibility between the parties to the obligation; с) joint responsibility of participants in the interaction process for joint decisions in the formation and implementation of family policy. The peculiarity of joint and separate obligations between the subjects of the formation and implementation of family policy is that the state (public) has the right to demand from any family member or from the family as a whole to fulfill the obligation. At the same time, family members alone or one of the family members can demand from the state, the public or from them together, high-quality and complete services. Such obligatory relations between the subjects of the formation and implementation of family policy are subdivided into “direct relations” and “regressive relations”. “Direct relationship” involves the interaction of the subjects of the formation and implementation of family policy. Each subject of the formation and implementation of family policy has the right to demand. The nature of “regressive relations” in solidary and separate obligations arises when one of the subjects of the formation and implementation of family policy applies to one of the family members in full. The fulfillment of the obligation by a family member completely terminates the obligations of the other joint beneficiaries to the service provider. At the same time, a family member who has solved a problem for everyone becomes a service provider for other family members who must fulfill their personal duty in the form of seeking help. However, these and other services are not provided in a coordinated manner. To solve this problem, the article proposes a comprehensive national electronic database of the “Family Service” type, which will receive information from various official sources.